Liver fluke infections by Amphimerus sp. (Digenea: Opisthorchiidae) in definitive and fish intermediate hosts in Manabí province, Ecuador - Romero-Alvarez, Daniel; Valverde-Muñoz, Gabriela; Calvopina, Manuel; Rojas, Maira; Cevallos, William; Kumazawa, Hideo; Takagi, Hidekazu; Sugiyama, Hiromu (PLOS Neglected Tropical Diseases, 2020)
Amphimerus sp. is a fluke that dwells in the biliary tracts of vertebrate definitive hosts including humans, domestic, and wild mammals in Latin America. Opisthorchiid liver infections are rarely studied in the Americas confirming its status as a neglected tropical disease. In Ecuador, small trematode eggs were reported in human cases from the province of Manabí in 1949, and recently, Amphimerus sp. adults were recovered from human and reservoir hosts in the province of Esmeraldas. Due to the lack of research on the infectious sources of Amphimerus sp. in the continent, we have developed a series of epidemiological studies with parasitological and molecular techniques to elucidate the endemicity of opisthorchiid fluke infections. We developed a cross-sectional study in three communities at Pedro Pablo Gómez parish in the province of Manabí, Ecuador. We examined a total of 176 fecal samples to detect opisthorchiid eggs, and four fish species to find opisthorchiid metacercariae. To study adult worms, we treated and purged seven patients in a family and dissected the livers of a dog and a cat infected. We observed morphological features of adults and metacercariae and used polymerase chain reaction with restricted fragment length polymorphism (PCR-RFLP) and DNA sequencing of a section of the ITS2 gene for identification. Small trematode eggs were detected in 63 (35.8%) out of 176 fecal samples of residents in the three study sites. Adult opisthorchiid flukes were recovered from human patients, a dog and a cat, and they were morphologically and molecularly identified as Amphimerus sp. Opisthorchiid metacercariae were also identified molecularly as Amphimerus sp. in four fish species, i.e., Rhoadsia altipinna, Bryconamericus bucay, Andinoacara rivulatus, and Piabucina aureoguttata. Metacercariae of the heterophyid Haplorchis pumilio were also found in the four fish species examined. This is the first study to confirm the current endemicity of Amphimerus sp. in Pedro Pablo Gómez, Manabí, Ecuador. The adult worms isolated here shared morphological characteristics with previous Amphimerus sp. descriptions and were molecularly similar to Amphimerus sp. described in the province of Esmeraldas. Moreover, this study is the first to document four fish species as infection sources of Amphimerus sp. detected via a molecular protocol targeting the metacercariae of the parasite. Fish species identified here should be targeted for public health campaigns to avoid further human liver-fluke infections by Amphimerus sp. or potential intestinal-fluke infections by H. pumilio or others.